2017
DOI: 10.1212/wnl.0000000000004674
|View full text |Cite|
|
Sign up to set email alerts
|

Quinidine-associated skin discoloration in KCNT1 -associated pediatric epilepsy

Abstract: A 9-month-old boy with migrating partial seizures of infancy due to a de novo KCNT1 mutation c.2278A.T (p.Ile760Phe) developed bluish discoloration of the hands, feet, and lips (figure) during a 9-month trial of quinidine (40 mg/kg/d; level 3.4 mg/mL).1 There was no exposure to other medications that cause pigmentary changes. Given minimal improvement in seizures and development, quinidine was stopped. Discoloration persisted at 3 months but markedly improved by the 6-month follow-up. Though common with other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Epilepsy (ADNFLE) and Ohtahara syndrome (Heron et al, 2012;Martin et al, 2014). To date, around 60 patients associating KCNT1 mutations and EIMFS are reported with variable and often incomplete information on seizures, EEGs, therapies, MRI and neurodevelopmental status (McTague et al, 2018;Ishii et al, 2013;McTague et al, 2013;Bearden et al, 2014, Mikati et al, 2015bMøller et al, 2015;Ohba et al, 2015;Mori et al, 2016;Rizzo et al, 2016;de Kovel et al, 2016;Baumer and Sheehan, 2017;Zhang et al, 2017;Jee N et al, 2017;Kawasaki et al, 2017;Madaan et al, 2017;Abdelnour et al, 2018;Numis et al, 2018;Dilena et al, 2018). Many questions remain unanswered, mainly on the prognosis and the long-term outcome.…”
Section: Mutations Of This Gene Have Been Also Reported In Autosomal mentioning
confidence: 99%
“…Epilepsy (ADNFLE) and Ohtahara syndrome (Heron et al, 2012;Martin et al, 2014). To date, around 60 patients associating KCNT1 mutations and EIMFS are reported with variable and often incomplete information on seizures, EEGs, therapies, MRI and neurodevelopmental status (McTague et al, 2018;Ishii et al, 2013;McTague et al, 2013;Bearden et al, 2014, Mikati et al, 2015bMøller et al, 2015;Ohba et al, 2015;Mori et al, 2016;Rizzo et al, 2016;de Kovel et al, 2016;Baumer and Sheehan, 2017;Zhang et al, 2017;Jee N et al, 2017;Kawasaki et al, 2017;Madaan et al, 2017;Abdelnour et al, 2018;Numis et al, 2018;Dilena et al, 2018). Many questions remain unanswered, mainly on the prognosis and the long-term outcome.…”
Section: Mutations Of This Gene Have Been Also Reported In Autosomal mentioning
confidence: 99%
“…Gain of function variants in KCNT1 have also been found in patients with other epileptic syndromes including Autosomal Dominant Nocturnal Frontal Lobe Epilepsy, Ohtahara syndrome, and Lennox-Gastaut syndrome (3,5,7,8,20,21). The antiarrhythmic drug quinidine has been shown to reduce the pathogenic currents produced by some of the mutant KCNT1 channels in vitro (11,17,(22)(23)(24)(25) but has had a limited clinical translation due to unwanted side effects (QTc prolongation and increased risk for arrhythmia) thereby resulting in a limited therapeutic window (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). To date, there is no effective therapy to treat KCNT1 associated epilepsies.…”
Section: Introductionmentioning
confidence: 99%
“…The search yielded 319 records of which 138, 151 and 30 were from PubMed, Embase and Cochrane Online Library databases, respectively. Of these, only 27 studies met the inclusion and exclusion criteria, and were thus analysed in this study; 25 studies reported on the effect of quinidine in patients with KCNT1 ‐related epileptic disorders and six studies tested the effect of quinidine in Kcnt1 mutations in vitro 5,7–10,15–36 . The study identification procedure is illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%